Associação entre doença periodontal e infarto agudo do miocárdio - Farias, Naiara Silva Aragão (2010)
Periodontal disease has been suggested as a risk factor for some systemic complications such as acute myocardial infarction, although there are many controversies on this subject. Accordingly, this case-control study that was conducted in two hospitals in the city of Feira de Santana - Bahia - Brazil, intended to study a possible association between these two diseases. Of the 458 eligible individuals the sample consisted of 290 participants, 216 controls and 74 cases. The cases were those patients with a diagnosis of acute myocardial infarction according to the inclusion criteria. The controls in turn, were the companions of the cases and companions of the other patients, admitted in these hospitals. Throughout the study was conducted using descriptors as measures of clinical care, probing depth of the sulcus / pocket, recession or gingival hyperplasia, clinical attachment level (CAL), plaque index, bleeding on probing. Enabling the later diagnosis of periodontal disease, which classified the subjects with severe periodontitis (those with 30% of teeth with CAL ≥ 5 mm) and individuals without severe periodontitis (those with less than 30% of teeth with CAL ≥ 5 mm). For acute myocardial infarction was performed electrocardiogram, serum CK (MB) and troponin within the criteria established by the Brazilian Society of Cardiology. Data analysis was employed by the descriptive analysis between the covariates of interest and the outcome, stratified and multivariate analysis using logistic regression. Comparison of proportions was performed using the chi-square. Measures of association (odds ratio) and the adjusted for confounders were taken on a significance level of 5%. The results showed a main measure of association unadjusted OR = 2.52 (95% CI [1.38 - 4.70]), statistically significant, and when adjusted for age, sex, education level, smoking, hypertension and diabetes this measure was ORadjusted of 1.51 (95% CI [0.73 - 3.14]), losing statistical significance. Epidemiologically, this means that the individual with severe periodontitis is approximately one and half times more likely to have AMI, even after adjusting for confounding factors.